Timing and Resource Analysis of Emergency Response Process Using Petri Nets - Lin Zhao; Hongxia Li; Jiacun Wang; Lei Chen (IEEE Access)
Emergency response is any systematic response to unexpected events that pose potential risk and/or damage to human life or property. Outbreak of virus, leak of poisonous chemicals, and terrorist attack are just a few examples. The goal of emergency response is to minimize the adverse impact of an incident to society and the environment. To guarantee the implementation of its handling procedure, adequate resources must be available. The success of emergency response also relies on the timeliness of related rescue actions. This paper presents resource-oriented timed workflow nets for the modeling and analysis of the resource requirements in responding to an emergency incident, as well as the time required to complete prescribed response tasks. This new model provides a formal basis for process designers and practitioners to examine the readiness and efficiency of their emergency plans. The presented algorithm can be applied to workflows with sequential, concurrent, decision-making and repetitive structures. A case study on chemical spill response is presented to illustrate the application of the proposed model.